Wheat Variety Test Results for South Central Kansas - 2021 - J. Seiler; R. Hein; R. Flaming; J. Carr; K. Nordyke; R. Lollato; B. C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2022)
South central Kansas is an important winter wheat production area in the state. This report summarizes the results of winter wheat variety tests for 2020-2021 in five locations.
Keywords: Grain yield; wheat yield; wheat production; winter wheat